Photoperiod-independent diurnal feeding improved the growth and feed utilization of juvenile rainbow trout (Oncorhynchus mykiss) by inducing food anticipatory activity - Xu, Hanying; Shi, Ce; Ye, Yangfang; Mu, Changkao; Wang, Chunlin (Frontiers in Marine Science, 2022)
A three-month culture experiment was designed to assess the effects of photoperiod and feeding regime on growth, feed utilization, and food anticipatory activity (FAA) of juvenile rainbow trout. The experiment included two photoperiods: 24L:0D (LL) and 12L:12D (LD); three feeding regimes: random feeding (R), mid-dark stage feeding (D), and mid-light stage feeding (L). A total of six treatment groups (R-LL, D-LL, L-LL, R-LD, D-LD, L-LD) were defined. The experimental results showed that the growth and feed utilization of the scheduled feeding groups (D and L groups) were significantly higher than those of the R group under both photoperiods, and there was no statistical difference between the D and L groups. A typical FAA was observed in the L group, independent of the photoperiod. Also, the digestive enzyme activity of the L group was synchronized by the feeding time under both photoperiods. There were rhythms in serum levels of glucose (GLU), triglyceride (TG), and total-cholesterol (T-CHO) in the D and L groups. Serum GLU also had a rhythm in the R group, but the peaks occurred at the feeding point (LL group) or after the feeding point (LD group), reflecting a possible passive rise in GLU after feeding. Serum cortisol was higher in the R group than in the scheduled feeding group, indicating that random feeding caused stress to juvenile rainbow trout. Serum insulin levels were found to increase before feeding in all three feeding regimes, probably reflecting the anticipation of food induced by the last meal. Serum melatonin levels were suppressed by the LL group. Serum 5-HT levels were synchronized by meal time in the R and L groups. Finally, rhythms of appetite-related genes were observed under all three feeding regimes, and more genes were rhythmic under LL, suggesting that food can strongly synchronize the feeding rhythm of juvenile rainbow trout when lacking light zeitgeber. In summary, this study concluded that diurnal feeding (L group) independent of photoperiod induced typical FAA in juvenile rainbow trout and that the LD (12L:12D) photoperiod and L (mid-light phase) feeding were recommended in the juvenile rainbow trout aquaculture.